“DUAL CAREER”: CASE STUDY IN ELITE SPORTS - Simona OROS; Iacob HANȚIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
During their high performance sports career, athletes commit themselves to fulfil several roles, being at the same time students, family members or employees, being challenged to meet the requirements of a dual career: an active, sportive and educational/professional one. The timespan of a “dual career” for a sportive is a complex one and requires effort and sacrifices, as well as support from the family, school and sporting environment that should help in the achievement of a balanced development. The present endeavour is a case study which wishes to present a global image of the educational, professional formation route, developed in parallel with the high performance sports activity, all framed within the concept of “dual career”. It is a qualitative research in which the interview method has been used, the analysed case being considered a model of success in high performance sports. The conclusions of this study emphasize the complexity of the phenomenon, as well as the need to responsibly manage the two careers, involving both the sportive and educational/professional formation.